(untitled) (Ameghiniana, 2014)
Nemagraptid and diplograptid graptolites from the Empozada Formation deposited in the ""Juan Cornelio Moyano"" Natural and Anthropological Seienees Museum of Mendoza are revised. The collection was made by Carlos Rusconi during the 1940’s and the 1950’s from several outcrops of this formation, located in the San Isidro area of the southern Mendoza Precordillera. This material was compared with specimens from the same unit collected by the authors. The types and paratypes of ten nominal species described by Rusconi were examined and assigned to Nemagraptus gracilis (Hall), Climacograptus bicornis (Hall), Climacograptus tridentatus Lapworth, Climacograptus tubuliferus Lapworth, and Climacograptus d. C. caudatus Lapworth. In addition, a specimen of Pseudoclimacograptus scharenbergi (Lapworth) is described.